Readyness for Biodiversity Accounting Disclosure in Corporations Towards Future Hilirization - Zai, Simon Nisja Putra; Widianingsih, Yuni Pristiwati Noer (Dinasti Publisher, 2025)
This study examines biodiversity accounting in Indonesia's mining and energy sectors, highlighting the challenges and readiness of companies to support the downstream agenda. Despite the increasing importance of biodiversity for sustainability, issues such as transparency in environmental cost reporting and compliance with regulations persist. Using a qualitative approach through textual analysis of sustainability reports from 60 companies listed on the Indonesia Stock Exchange for 2022-2023, the research identifies key themes related to biodiversity impacts and company actions. The findings reveal that these companies exhibit varying levels of readiness in facing downstream initiatives, with a significant gap between corporate commitments to biodiversity protection and actual implementation. Recommendations for future studies emphasize the importance of integrating advanced technologies, stakeholder engagement, and the role of policy frameworks in enhancing biodiversity management. This research contributes to understanding how companies can align their practices with sustainable development goals, ensuring economic growth while safeguarding biodiversity.